PENYULUHAN TENTANG PENCEGAHAN PENULARAN COVID – 19 DI KOTA BENGKULU - Dwiana Maydinar, Dian; Juksen, Loren; Colin, Vellyza; Sazarni Ratiyun, Rafidaini (COVIT (Community Service of Tambusai), 2021)
COVID-19 can spread from person to person especially when an infected person is in close contact with other people. One of the efforts to break the chain of spread of COVID-19 is to prevent COVID-19 which requires understanding and knowledge and good and correct behavior from all elements including nurses. The purpose of this counseling activity is to add insight and knowledge for nurses and can increase nurse awareness to carry out prevention and self-protection efforts as well as carry out health protocols during the COVID-19 pandemic. This activity was carried out at the Bengkulu City Health Center. This activity began by asking questions about knowledge about COVID-19. Followed by giving material using power point and giving leaflets. The result of this activity was an increase in knowledge about COVID-19 by 90%. This activity is the first step to increase knowledge to carry out daily life. Keywords: Counseling, Prevention of COVID-19